Human and environmental health at risk: An approach to the practice of urban burning - da Silva , Marivaldo Cavalcante; Lopes, Alberto Pereira; Pereira, Aires José (Seven Editora, 2024)
High temperatures have provided risks to human and environmental health at various levels and scales in several countries around the globe. This work aims to contribute to a reflection on urban burning practices with a view to the impacts on human and environmental health. It presents a consistent and updated theoretical basis on the problem, having as an urban space to reflect on the problem, the city of Araguaína in Tocantins. Several countries have recorded an increase in the case of urban and rural fires and large fires with traces of devastation and deaths, as occurred in Chile, the United States, Canada and Brazil. DOI:https://doi.org/10.56238/sevened2024.025-018